Input-Output Admissibility Analysis of Continuous Descriptor System with Time-Varying Delay - Acosta-Barbosa, K; El Aiss-Berazouq, H (Institute of Electrical and Electronics Engineers Inc., 2021)
This letter deals with the input-output admissibility analysis of the continuous descriptor system with a time-varying delay. A two-term approximation transformation-model has been used to convert the original system into two interconnected subsystems. Based on the scaled small gain theorem and a new Lyapunov-Krasovskii functional, a delay-dependent sufficient condition has been presented to ensure that the time-varying delay descriptor system is input-output stable, regular, and impulse free. The derived conditions are given in a set of linear matrix inequalities. Finally, an example has been used to test the merit and validity of the proposed method. © 2017 IEEE.